Students' Problem-solving Ability in Geometry during the Covid-19 Pandemic - Fini Rezy Enabela Novilanti; Weni Dwi Susanti; Suripah Suripah (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Currently, the learning process is still done online. This is a challenge for teachers to continue to apply problem-solving skills in the mathematics learning process. One of the appropriate mathematics materials to measure students' problem-solving abilities is geometry. Geometry material is often an obstacle for students because geometry material is abstract. Therefore, teachers must analyze students' problem-solving skills during the COVID-19 pandemic, especially geometry material. The purpose of this study was to describe students' problem-solving ability in answering geometry questions given by the teacher. This study uses descriptive qualitative research because of the Covid-19 pandemic. The subjects used were 20 students of grade VIII from one of the schools in Pekanbaru. The sampling technique used in this research is purposive sampling technique. The instruments used are test instruments, interviews, and documentation of student answers. Data analysis used was descriptive qualitative method referring to the Polya error indicator. The results of this study indicate that students' problem-solving abilities are still relatively low. This can be seen from some students experiencing difficulties solving the given geometry problems. So that teachers must be able to improve students' problem-solving abilities.